The role of chemical structure in indacenodithienothiophene-alt-benzothiadiazole copolymers for high performance organic solar cells with improved photo-stability through minimization of burn-in loss. Issue 47 (27th November 2017) - Chochos, Christos L.; Leclerc, Nicolas; Gasparini, Nicola; Zimmerman, Nicolas; Tatsi, Elisavet; Katsouras, Athanasios; Moschovas, Dimitrios; Serpetzoglou, Efthymis; Konidakis, Ioannis; Fall, Sadiara; Lévêque, Patrick; Heiser, Thomas; et al.
Abstract : The organic solar cell initial burn-in loss is suppressed via the rational design of the polymer's chemical structure. Abstract : It is of upmost importance to gain an in-depth understanding of the role of the polymer chemical structure in the performance of the corresponding organic solar cell (OSC) and its degradation behavior, which is currently insufficiently explored. Achieving these correlations will set new design rules towards further optimization of polymer chemical structures for OSCs exhibiting high performances and long stability. In this study, our efforts have been focused on identifying how the nature of aryl substituents and the number of fluorine atoms anchored in the backbone of indacenodithieno[3, 2- b ]thiophene (IDTT) based polymers influence their optoelectronic properties, the OSC performances and their degradation mechanisms. The most important outcome of this study is the demonstration that standard initial burn-in loss is primary attributed to microstructure instabilities. Furthermore, the initial burn-in loss could be substantially reduced through the rational design of the polymeric semiconductor's chemical structure, leading to improved lifetimes and low (20%) initial power conversion efficiency loss. In particular, we identify the beneficial effect of the presence of the two fluorine atoms on the benzo[ c ][1, 2, 5]thiadiazole (BTD), as compared to the non-fluorinated and mono-fluorinated analogues, in decreasing the burn-in by reducing the microstructure instabilities regardless of the aryl substituent that is present in the polymer backbone.